Altered Gray Matter Volume and Functional Connectivity in Patients With Vestibular Migraine - Zhe, Xia; Zhang, Xiaoling; Chen, Li; Zhang, Li; Tang, Min; Zhang, Dongsheng; Li, Longchao; Lei, Xiaoyan; Jin, Chenwang (Frontiers in Neuroscience, 2021)
Abstract Subjects: Vestibular migraine (VM) is the most common neurological cause of vertigo in adults. Previous neuroimaging studies have reported structural alterations in areas associated with pain and vestibular processing. However, it is unclear whether altered resting-state functional connectivity exists in brain regions with structural abnormalities in patients with VM. Methods: Resting-state functional magnetic resonance imaging (MRI) and three-dimensional T1-weighed MRI were performed in 30 patients with VM and 30 healthy controls (HCs). Patients underwent an evaluation of migraine and dizziness severity. Functional connectivity (FC) and voxel-based morphometry were performed using DPABI 4.3 and CAT12, respectively. The association between changes in gray matter (GM) volume or FC and clinical parameters was also analyzed. Results: Compared with HCs, patients with VM demonstrated a reduced GM volume in the bilateral parietoinsular vestibular cortex (PIVC), right middle frontal gyrus, and precuneus. The GM volume of the left PIVC was negatively associated with Dizziness Handicap Inventory score in patients with VM. Taking this region as a seed region, we further observed increased FC between the left primary somatosensory cortex (S1)/inferior parietal lobule (IPL) and the left PIVC in patients with VM. Conclusions: FC between regions with a decline in GM volume (the PIVC and S1/IPL) is altered in patients with VM, suggesting that abnormalities in central pain-processing pathways may be involved in the pathophysiology of VM.